The Role of Islamic Religious Education and Majelis Taklim in Enhancing Community Religiosity - Mukhtar Mas’ud (Program Pascasarjana UIN Sumatera Utara, 2023)
This study aims to analyze the correlation between Islamic Religious Education and Majelis Taklim in strengthening community religiosity in the era of globalization. This research employed a qualitative approach using library research and content analysis methods. Data were obtained from Qur’anic verses, hadith, Islamic education textbooks, scholarly journals, and laws and regulations related to religious education. The findings indicate a strategic correlation between Islamic Religious Education and Majelis Taklim in four main areas, namely education, religion, social community life, and profession. Islamic Religious Education provides a structured foundation of knowledge, while Majelis Taklim functions as a practical and contextual reinforcement. The synergy between the two is able to overcome the limitations of formal learning and strengthen the internalization of Islamic values in everyday life. This study concludes that collaboration between Islamic Religious Education and Majelis Taklim is an effective strategy for shaping a society that is faithful, pious, and morally upright. The study recommends strengthening cooperation between Islamic Religious Education teachers and Majelis Taklim administrators through scheduled joint programs and policy support from the government. Thus, community religiosity is expected to grow and become stronger amid various contemporary moral challenges.